Multiprofessional duty transfer: integrative literature review (Research, Society and Development, 2022)
Objective: Know the practices of transferring responsibility between on-duty workers in the intensive care unit in fulfilling goal two in ensuring patient safety through an integrative review. Methodology: The research is characterized as an Integrative Literature Review - RIL, this method allows inferring results from multiple previously published studies. Results: After all the methodological procedure, the search resulted in a total of 59 articles. Of these, 24 were found in the PubMed database, 33 in the Google Scholar platform, and 02 in LILACS, the other platforms did not present results that were in accordance with the selection criteria. Therefore, 54 of these did not meet the eligibility criteria of the present study. Conclusion: Although this study has a multidisciplinary approach, it was noted that most of the published content is related to the practices of the nursing team, with a gap in specific content of the medical team and other professionals. Therefore, it is suggested that researchers and scholars turn their attention to this subject, especially those belonging to the field of medicine, in order to provide better possibilities to provide professional assistance free from risks and harm to the safety of patients and to contribute to the production science in this area.